Resveratrol Attenuate Myocardial Injury by Inhibiting Ferroptosis Via Inducing KAT5/GPX4 in Myocardial Infarction - Liu, Jing; Zhang, Mingming; Qin, Chaoshi; Wang, Zikuan; Chen, Jianghong; Wang, Rui; Hu, Jianqiang; Zou, Qing; Niu, Xiaolin (Frontiers in Pharmacology, 2022)
Myocardial infarction (MI) is a coronary artery-related disease and ranks as the leading cause of sudden death globally. Resveratrol (Res) is a bioactive component and has presented antioxidant, anti-inflammatory and anti-microbial properties. However, the effect of Res on ferroptosis during MI progression remains elusive. Here, we aimed to explore the function of Res in the regulation of ferroptosis and myocardial injury in MI. We observed that the treatment of Res attenuated the MI-related myocardium injury and fibrosis in the rats. The expression of collagen 1 and α-SMA was induced in MI rats, in which the treatment of Res could decrease the expression. Treatment of Res suppressed the levels of IL-6 and IL-1β in MI rats. The GSH levels were inhibited and MDA, lipid ROS, and Fe2+ levels were induced in MI rats, in which the treatment of Res could reverse the phenotypes. Meanwhile, the expression of GPX4 and SLC7A11 was reduced in MI rats, while the treatment of Res could rescue the expression in the model. Meanwhile, Res relieved oxygen-glucose deprivation (OGD)-induced cardiomyocyte injury. Importantly, Res repressed OGD-induced cardiomyocyte ferroptosis in vitro. Mechanically, we identified that Res was able to enhance GPX4 expression by inducing KAT5 expression. We confirmed that KAT5 alleviated OGD-induced cardiomyocyte injury and ferroptosis. The depletion of KAT5 or GPX4 could reverse the effect of Res on OGD-induced cardiomyocyte injury. Thus, we concluded that Res attenuated myocardial injury by inhibiting ferroptosis via inducing KAT5/GPX4 in myocardial infarction. Our finding provides new evidence of the potential therapeutic effect of Res on MI by targeting ferroptosis.